Object and event reconstruction (WW. II.) with GIS - Juhász, Attila; Mihályi, Balázs (Acta Agraria Kaposváriensis, 2004)
In our days GIS increasingly becomes popular in humane disciplines. In our research we use it to support military historical reconstruction. We deal with the Attila-line, which was a defence line around Budapest in the World War II. Our goal was a particular and dependable reconstruction, which contains environmental, object and, event parts. To get through with this task we had to collect and manage a lot of variable-quality archive data. This information comes from different sources: libraries, archives, archive maps and arial photos, field measrements, and personal reminiscences. We can manage this information in a standard system with GIS. This database can be used as a reference system to support further research and to identify new parts of the defence line. Using the attributes we can make queries and various reviews. The database is usable as a digital data archive, too. Our next research goal is to follow the search of the Attila-line and other defence lines and to present them to wider scientific and public audiance.
Keywords: GIS; military historical; object reconstruction; Attila-line